Identification of transient overvoltage using discrete wavelet transform with minimised border distortion effect and support vector machine - Asman S.H.; Abidin A.F.; Yusoh M.A.T.M.; Subiyanto S. (Elsevier B.V., 2023)
Discrete wavelet transforms; Electrolysis; Power quality; Signal reconstruction; Border distortion; Discrete-wavelet-transform; Distortion effects; Sliding Window; Support vector machine classification; Support vectors machine; Transient disturbances; Transient overvoltages; Transient signal; Window techniques; Support vector machines